APPLICATION EXPERIENCE OF CETIRIZINE SYRUP IN THE TREATMENT OF ATOPIC DERMATITIS AMONG CHILDREN - I.V. Makarova; R.N. Arakelyan; N.B. Bal'tserovich; S.G. Lazareva; E.V. Mukharaeva (Union of pediatricians of Russia, 2007)
The article gives the findings of the scientific research, whose purpose was to study the impact of cetirizine syrup (Zodiac, Zentiva, Czech Republic) on the run of atopic dermatitis among 36 children aged between 2 and 6 years old. The work shows that introduction of the medication into the complex therapy of atopic dermatitis among children provides a fast clinical effect. Cetirizine syrup is well tolerated by the children.Key words: atopic dermatitis, children, cetirizine, treatment.